Implementation Of Islamic Religious Education Learning Process at SMP Bani Adam 'As Mabar - Siti Nurhasanah (-, 2023)
In the research conducted at the Bani Adam 'As Mabar Junior High School includes the implementation, implications, supporting factors and inhibiting factors of the implementation of the Islamic Religious Education learning process. This study uses a qualitative method based on events in the field. The research data were collected through observation, interviews, documentation, analysis and data presentation. From the results of this study it can be stated that: the implementation of the Islamic Religious Education learning process at Bani Adam 'As Middle School includes curriculum coverage, KTSP concepts, processes and evaluations. Then the implications of the learning process at SMP Bani Adam 'As in increasing the religious understanding of grade VII students have a very positive influence on increasing their understanding. Supporting factors include: the ability of teachers or students, the provision of learning tools or media and support from the principal. and the inhibiting factors are: difficulty dealing with student characteristics and the atmosphere outside the classroom which is quite disturbing.